Cyclists' improvement of pedaling efficacy and performance after heavy strength training - Hansen, E. A.; Rønnestad, B. R.; Vegge, G.; Raastad, T. (International Journal of Sports Physiology and Performance, 2012)
The authors tested whether heavy strength training, including hip-flexion exercise, would reduce the extent of the phase in the crank revolution where negative or retarding crank torque occurs. Negative torque normally occurs in the upstroke phase when the leg is lifted by flexing the hip. Eighteen well-trained cyclists either performed 12 wk of heavy strength training in addition to their usual endurance training (E+S; n = 10) or merely continued their usual endurance training during the intervention period (E; n = 8). The strength training consisted of 4 lower body exercises (3 × 4-10 repetition maximum) performed twice a week. E+S enhanced cycling performance by 7%, which was more than in E (P = .02). Performance was determined as average power output in a 5-min all-out trial performed subsequent to 185 min of submaximal cycling. The performance enhancement, which has been reported previously, was here shown to be accompanied by improved pedaling efficacy during the all-out cycling. Thus, E+S shortened the phase where negative crank torque occurs by ~16°, corresponding to ~14%, which was more than in E (P = .002). In conclusion, adding heavy strength training to usual endurance training in well-trained cyclists improves pedaling efficacy during 5-min all-out cycling performed after 185 min of cycling.